Comparing thousands of circular genomes using the CGView Comparison Tool - Grant, Jason R; Arantes, Adriano S; Stothard, Paul (BMC genomics, 2012)
Background Continued sequencing efforts coupled with advances in sequencing technology will lead to the completion of a vast number of small genomes. Whole-genome comparisons represent an important part of the analysis of any new genome sequence, as they can provide a better understanding of the biology and evolution of the source organism. Visualization of the results is important, as it allows information from a variety of sources to be integrated and interpreted. However, existing graphical comparison tools lack features needed for efficiently comparing a new genome to hundreds or thousands of existing sequences. Moreover, existing tools are limited in terms of the types of comparisons that can be performed, the extent to which the output can be customized, and the ease with which the entire process can be automated. Results The CGView Comparison Tool (CCT) is a package for visually comparing bacterial, plasmid, chloroplast, or mitochondrial sequences of interest to existing genomes or sequence collections. The comparisons are conducted using BLAST, and the BLAST results are presented in the form of graphical maps that can also show sequence features, gene and protein names, COG (Clusters of Orthologous Groups of proteins) category assignments, and sequence composition characteristics. CCT can generate maps in a variety of sizes, including 400 Megapixel maps suitable for posters. Comparisons can be conducted within a particular species or genus, or all available genomes can be used. The entire map creation process, from downloading sequences to redrawing zoomed maps, can be completed easily using scripts included with the CCT. User-defined features or analysis results can be included on maps, and maps can be extensively customized. To simplify program setup, a CCT virtual machine that includes all dependencies preinstalled is available. Detailed tutorials illustrating the use of CCT are included with the CCT documentation. Conclusion CCT can be used to visually compare a reference sequence to thousands of existing genomes or sequence collections (next-generation sequencing reads for example) on a standard desktop computer. It provides analysis and visualization functionality not available in any existing circular genome visualization tool. By visually presenting sequence conservation information along with functional classifications and sequence composition characteristics, CCT can be a useful tool for identifying rapidly evolving or novel sequences, horizontally transferred sequences, or unusual functional properties in newly sequenced genomes. CCT is freely available for download at http://stothard.afns.ualberta.ca/downloads/CCT/ .